ASSESSING EDUCATIONAL INSTITUTIONS WITH MMEI - kumari, arisha; g, payal; KUMARESH, shakti (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
An investment in knowledge pays the best interest. Says Benjamin Franklin but an investment in the best educational institution pays the biggest interest. Defining the best institution is one of the major challenges. Educational institutions vary from the most reputed to undistinguished institutions. There are certification agencies like Washington Accord (International Engineering Alliance, www.washingtonaccord.org) that consists of six international agreements used to govern mutual recognition of engineering qualifications and professional competence. Also there are National bodies like NBA (National Board of Accreditation - India) for the purpose of assessment of Quality and Accreditation of Technical programmes in India. But these bodies work like certification agencies. We require processes that help and govern institutions to reach the most distinguished level. Just as CMMI is used in software industry to judge the maturity of the software processes, in this paper we propose an assessment and improvement framework for all educational institutions. This framework would help institutions to be ranked in levels and also help them to achieve higher levels. MMEI Maturity Model for Educational Institution is a model that proposes a system which would help any educational institution to be ranked among the most distinguished ones